2017
DOI: 10.2967/jnmt.117.198408
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method to Detect and Characterize 18F-FDG Infiltration at the Injection Site: A Single-Institution Experience

Abstract: A novel quality control and quality assurance device provides time-activity curves that can identify and characterize PET/CT radiotracer infiltration at the injection site during the uptake phase. The purpose of this study was to compare rates of infiltration detected by the device with rates detected by physicians. We also assessed the value of using the device to improve injection results in our center. 109 subjects consented to the study. All had passive device sensors applied to their skin near the injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…LARA systems were set up in 3 injection/uptake rooms. In each uptake room, LARA sensors (Lucerno Dynamics) were applied to the subject using adhesive pads 7 cm proximal to the injection site and the same site on the contralateral arm (reference arm) (as previously described; [7]). These sensors were connected to a small recording device which sits in a holder nearby.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LARA systems were set up in 3 injection/uptake rooms. In each uptake room, LARA sensors (Lucerno Dynamics) were applied to the subject using adhesive pads 7 cm proximal to the injection site and the same site on the contralateral arm (reference arm) (as previously described; [7]). These sensors were connected to a small recording device which sits in a holder nearby.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, an analysis of 1367 patient studies, 18% demonstrated extravasation which was quantitated to represent between 1% and 22% of the injected dose [6]. A smaller single-centre analysis reported 38% of patients with extravasated doses [7]. Although an indication of dose extravasation may include pain or swelling at the site of injection, visual evaluation of images post-PET procedure is perhaps the most common approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining pulses are then counted to produce a sensor output in counts per second (cps). For this proposed clinical use, the sensor, along with a second sensor placed on the contralateral arm to collect reference data, could identify the presence of excessive residual radiotracer near the injection site . Both sensors would then be removed prior to imaging.…”
Section: Introductionmentioning
confidence: 99%
“…For this proposed clinical use, the sensor, along with a second sensor placed on the contralateral arm to collect reference data, could identify the presence of excessive residual radiotracer near the injection site. 50,51 Both sensors would then be removed prior to imaging. Based on the sensor design, it may not be possible to provide absolute quantification of the radiotracer near the injection site, but a semi-quantitative assessment would still be valuable.…”
Section: Introductionmentioning
confidence: 99%